Pengaruh Return On Asset (ROA) Dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Manufaktur yang Terdaftar di Indonesia Periode 2017-2019 - Mahdi Hendrich (Jurnal Ilmiah Akuntansi Rahmaniyah, 2020)
This study attempts to examine how much influence these two variables, namely ROA and ROE, on stock prices, especially in manufacturing companies of the type of "Consumer Goods" listed on the Indonesia Stock Exchange, the Malaysia Stock Exchange and the Thailand Stock Exchange. The sampling technique used was purposive sampling based on certain criteria or considerations. The sample taken is the financial statements of 9 companies that have been determined in accordance with the provisions of sampling with the period 2017-2019. The result shows that, simultaneously, Return On Asset (ROA) and Return On Equity (ROE) have a positive effect on stock prices in manufacturing companies in Indonesia. The coefficient of determination (R2) of 0.238 indicates that each share price is influenced by the ROA, ROE and State variables of 23.8% while the remaining 76.2% is influenced by other variables not examined.